Adoption of high‐performance work systems in small and medium‐sized enterprises. (8th March 2021) - Sun, Yiyang; Mamman, Aminu
Abstract : This paper investigates the factors influencing the adoption of high‐performance work systems (HPWS) in Chinese small and medium‐sized enterprises (SMEs). The paper is based on a sample of 207 SMEs, which covers many of the ownership types and business sectors. The results of the correlation and regression analyses indicate that organizational factors have stronger explanatory power in predicting the adoption of HPWS than institutional factors. Specifically, top management support, perceived impact of HPWS, and organizational size are the three main predictors. The findings suggest that using management innovation theories to understand the underlying reasons associated with the adoption of HPWS is promising. The paper argues for the use of management innovation theories to explore the efficacy of institutional factors more fully.